Scientific Communication Skills Profile of Prospective Science Teachers Based on Sociocultural Aspects - Taufiq, M.; Rokhman, F. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
One of the essential skills for future science teacher candidates is scientific communication, while the background of sociocultural aspects influences communication which must have a scientific basis. This research aims to analyse the scientific communication skills of prospective science teacher based on sociocultural aspects. Quantitative survey research methods applied in this research, using a questionnaire as a data collection tool. The population in this research were students of natural science education programs at one of the state universities in Semarang, Central Java, Indonesia, while the samples are 87 students. The results of this study indicate that the sociocultural aspects of students vary with the characteristics of the area of origin, regional languages, different languages, regional cultures, and different social attitudes. The sociocultural aspects are specified in two levels, which are Zone of Proximal Development (ZPD) and More Knowledgeable Other (MKO). At the ZPD level, 67% of the students are in the intermediate criteria and 33% in the advanced criteria. While at the MKO level, the criteria are intermediate and advanced, with percentages almost equal to 49% and 51%, respectively. It was concluded that the profile of scientific communication skills of prospective science teacher based on sociocultural aspects was in the intermediate and advanced criteria. Students are indicated to experience Ã¢â‚¬Å“vernacular misconceptionsÃ¢â‚¬Â related to the sociocultural aspects of the use of various languages used in daily communication and writing. The frequency is dominated by the use of regional languages that are not relevant to scientific languages. Further research needs to be carried out on the identification of scientific misconceptions related to sociocultural aspects.